Drivers of medicine spending in a public hospital in Rio de Janeiro Brazil from 2013 to 2020 (Research, Society and Development, 2022)
Medicines are important drives of health expenditure. To ensure that all patients have access to this technology is challenging given the financial constraints of health systems. The aim of this study was to analyze drug expenditures and their drivers in a public hospital located in Rio de Janeiro, Brazil, from 2013 to 2020. All data regarding drug purchases were retrieved from the database of the hospital Information System used to manage health products purchases. The pharmaceutical products were classified in accordance with the Anatomical, Therapeutic, and Chemical (ATC) classification system coordinated by the WHO Collaborating Centre for Drug Statistics Methodology and aggregated by volume and by expenditure. The expenditure variation was decomposed into three broad categories: price effects, quantity effects, and drug mix effects. During the period, annual expenditure reduced by 20%, ranging from from R$ 16.9 million in 2013 to R$ 13.4 million in 2020, while purchased quantities also dropped  by 33.7%, ranging from 5.7 million in 2013 to 3.8 million unites in 2020. Two factors drove the reducition of expenditures, the quantity effect and the price effect. These findings may contribute to better understanding medicine spending trends and the factors that influence them in order to formulate strategies to optimize resource utilization and improve patients access to the necessary tratments.